Crop Diversification and Environmental Conflicts in Kasaragod District of Kerala - N. Karunakaran (Agricultural Economics Research Review, 2014)
The agricultural sector of Kerala in general and of Kasaragod district in particular has witnessed a paradigm shift in the cropping pattern away from food crops towards non-food crops, and from one non-food crop to another non-food crop as to capture benefits of emerging markets. These changes have caused severe challenges to the environment in the form of land degradation, groundwater depletion and chemical pollution. To elicit the facts and issues connected with this changing paradigm, the analysis in this paper has shown a significant decline in soil fertility and groundwater level, and over-use of chemical fertilisers in the plantation-dominated Kasaragod district.